Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems 2023
DOI: 10.1145/3544548.3580744
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning Narrative Intelligence: A Creative Visual Storytelling Anthology

Abstract: In this paper, we collect an anthology of 100 visual stories from authors who participated in our systematic creative process of improvised story-building based on image sequences. Following close reading and thematic analysis of our anthology, we present five themes that characterize the variations found in this creative visual storytelling process: (1) Narrating What is in Vision vs. Envisioning; (2) Dynamically Characterizing Entities/Objects; (3) Sensing Experiential Information About the Scenery; (4) Modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Previously, HCI researchers also found that creative activities such as bullet journaling [5,87] or visual storytelling [39,91,92] can facilitate self-reflection and promote mindfulness through a creative meaning-making process. To track emotions, for example, bullet journalists were found to come up with individualised, decorative, and artistic representations of moods, such as Mandala, Origami, text narrative, etc [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, HCI researchers also found that creative activities such as bullet journaling [5,87] or visual storytelling [39,91,92] can facilitate self-reflection and promote mindfulness through a creative meaning-making process. To track emotions, for example, bullet journalists were found to come up with individualised, decorative, and artistic representations of moods, such as Mandala, Origami, text narrative, etc [5].…”
Section: Introductionmentioning
confidence: 99%